2008
DOI: 10.1677/joe-07-0497
|View full text |Cite
|
Sign up to set email alerts
|

FSH-induced phosphoprotein phosphatase 2A-mediated deactivation of particulate phosphodiesterase-4 activities is abolished after alteration in proteoglycan synthesis in immature rat Sertoli cells

Abstract: Cessation of rat testicular Sertoli cells proliferation around days 15-20 post partum is associated in vitro with the highest rise in rolipram-sensitive cAMP-catabolizing phosphodiesterase-4 activities (PDE4s) triggered by FSH during the early postnatal period. The transient nature of FSH-induced increase in PDE4s suggests concomitant changes in both PKA-mediated activation and subsequent deactivation of these activities. In this study, we demonstrated that the deactivation of FSH-stimulated particulate, but n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…The cAMP-PDE activity was detected using the method described in our previous report . To identify the cAMP-PDE4 activity, a specific inhibitor, rolipram, was added to the incubation mixture at a final concentration of 10 µmol L -1 (Levallet et al 2008). The PDE activity measured in the presence of rolipram was subtracted from the total activity to quantify the PDE4 activity.…”
Section: Introductionmentioning
confidence: 99%
“…The cAMP-PDE activity was detected using the method described in our previous report . To identify the cAMP-PDE4 activity, a specific inhibitor, rolipram, was added to the incubation mixture at a final concentration of 10 µmol L -1 (Levallet et al 2008). The PDE activity measured in the presence of rolipram was subtracted from the total activity to quantify the PDE4 activity.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, early increases in cAMP levels followed by an immediate drop in cAMP concentrations have already been well described in cell differentiation, particularly in Sertoli cells [58]. Indeed, before the cAMP increase, stimulation of Sertoli cells by gonadotropin leads to an activation of the ERK pathway, while following the peak of cAMP, gonadotropin activates the PKA pathway.…”
Section: Discussionmentioning
confidence: 81%
“…Effects induced by 5-HT4R stimulation are time-limited since PKA phosphorylation of 5-HT4R, GRK2 or PDE can be reversed by phosphatase (PP) activity [58]. PP1 and PP2, compartmentalized inside the mammalian cell [93], [94], account for the major phosphatase activities [56]; PP2 is however more particularly investigated because of its ability to dephosphorylate many signaling proteins [93].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 206 , 207 , 208 , 209 Accordingly, it has been shown that PP2A activity is stimulated by FSH and PKA. 210 , 211 Thus, FSH may contribute to PP1 and PP2A activation, which in turn dephosphorylate inhibitory serine residues on IRS2 or IGF1R stimulating their activity (Figure 6 ).…”
Section: Plausible Molecular Crosstalk Between Fsh ...mentioning
confidence: 99%